2015
DOI: 10.7226/jtfm.21.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Sustainability Barriers of Community Conservation Agreement as a Collaboration Management in Lore Lindu National Park

Abstract: The main problem of forest institutional arrangement is the issue of institutional sustainability in achieving sustainable forest ecosystem. This study aimed to explain the barriers of institutional sustainability Community Conservation Agreement (CCA) designed in Lore Lindu National Park (LLNP), in Indonesia, as a collaborative management of national parks. This study is of descriptive which used qualitative approach, i.e. asking open-ended questions, reviewing documentation and analyzing textual of community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This program was initiated by Non-Government Organizations (NGOs) in the early 2000s (Birner and Mappatoba, 2009). However, implementation of CCA has faced obstacles in terms of its structure and capacity (Massiri, 2015). This requires a new strategy if CCA is to achieve institutional sustainability as a self-governing institution.…”
Section: Introductionmentioning
confidence: 99%
“…This program was initiated by Non-Government Organizations (NGOs) in the early 2000s (Birner and Mappatoba, 2009). However, implementation of CCA has faced obstacles in terms of its structure and capacity (Massiri, 2015). This requires a new strategy if CCA is to achieve institutional sustainability as a self-governing institution.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the Strengthening the institutional capacity of FMU at resort level Implementation of community-based forest management requires the critical role of FMU on the resort level to provide services to community groups. The low institutional capacity, in many cases, is an obstacle to collaborative forest management (Massiri et al, 2015). The institutional capacity of the two FMUs studied was relatively in the low category, particularly at the resort level.…”
Section: Scientific Article Issn: 2087-0469mentioning
confidence: 93%
“…There are multiple interpretations of the roles, functions, and interpretations of CCA (Ichsan, 2008). Whereas Massiri et al (2015) found that despite CCA led clarity of users and clarity of resources, however, the rules at the operational level arranged in CCA were not in line with formal rules of national park management at the constitutional level (a nested enterprise problem). Furthermore, the allocations of CCA location were on the rehabilitation zone and utilization zone that become barriers to the sustainability of CCA because that rules do not support the sustainability of the livelihood of local communities.…”
Section: Introductionmentioning
confidence: 94%